Dakwah Komunitas Akhwat Sholihah Dalam Menanamkan Pemahaman Jilbab di Kota Kisaran, Kabupaten Asahan - Apriliani, Tien; Arifin, Zainal (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The numerous differences in clothing practices among Muslim women that do not align with Islamic guidelines continue to spark debate and controversy in society, serving as the primary reason for this research. The aim of this study is to explore the da'wah (Islamic preaching) strategies employed by KoAS in instilling understanding about women's clothing, particularly the jilbab, which, according to their interpretation, aligns with the true principles of Islamic Sharia. It also seeks to analyze the impact of these strategies on the communities they preach to. This research uses a qualitative method with a case study approach, including participatory observation, in-depth interviews, and document analysis. The findings show that KoAS employs a variety of da'wah approaches, including religious lectures, small group discussions, and religious social activities. The use of social media also plays a significant role in expanding their da'wah outreach. Regular evaluations and the adaptation of feedback from KoAS members are among the methods used to ensure the sustainability and effectiveness of their da'wah efforts.